Effects of Polyhalite and Doses Application After Anthesis on Yield, Quality and Postharvest Storage Shelf Life of MD2 Pineapples (Ananas comosus) - Mei Kying Ong; Cong Rong Cheng; Ching Ang Ong; Mehdi Maqbool; Noosheen Zahid (Journal of Food Quality)
Potassium fertilisation plays an important role in improving pineapple fruit weight and quality. Potassium chloride (KCl)-based compound fertilizer instead of potassium sulphate (K2SO4) is often used in the pineapple cultivation due to its cheaper cost. A naturally formed mineral fertiliser mined in the U.K. known as polyhalite is one of the K2SO4-based fertiliser suitable for use in pineapple cultivation, besides supplying other macronutrients, which include magnesium (Mg), calcium (Ca) and sulphur (S). This study aimed to evaluate the effects of polyhalite application after anthesis on yield, quality and postharvest storage shelf life of MD2 pineapples. Results showed that the average fruit weight increased by 12.8% with polyhalite dosage with significant increase recorded at the dose of 660 kg/ha. N, K, Mg, Ca and B levels in D leaf increased with polyhalite application. Pineapples treated with 660 kg/ha had slightly higher total soluble solids (11.30%), crude fibre content (28.50%), titratable acidity (13.30%) and sensory profile of overall acceptability (1.90%) compared with the control (without polyhalite application) at Day 13 of storage period. Thus, it can be concluded that polyhalite has the potential to serve as fertiliser source supplying K and secondary macronutrients such as Ca, Mg and S to enhance yield, quality and shelf life of pineapples grown in Malaysia.